Climate Change: An Inconvenient Maybe - Edwards, Gonzalo (Estudios de Economía, 2016)
The subject of Climate Change is here to stay for at least the rest of the 21stcentury. The extent to which climate change can be expected; the importance inits determination of anthropogenic factors, relative to natural causes; its impacton world agriculture, migration patterns and economic growth; the costs involvedand the best practices to mitigate the consequences, are all still subject togreat controversy and remain in the realm of the speculative, in spite of specificmatters where a relative consensus has been reached, and despite media effortsto show only the more alarmist view. It is this controversy that gives the name tothis essay, which advertently paraphrases former United States Vice-PresidentAl Gore’s movie An Inconvenient Truth.